The role of renewable energy and storage technologies in sustainable development: simulation in the construction industry - Anna Horzela-Miś; Jakub Semrau (Frontiers in Energy Research)
IntroductionThe increasing demand for sustainable energy solutions has become crucial in addressing global environmental challenges such as climate change and resource depletion. As a significant energy consumer, the construction industry must explore renewable energy integration to enhance sustainability. This study investigates the role of photovoltaic (PV) systems and energy storage technologies in promoting sustainable energy use within a Polish construction manufacturing company.MethodsA 26-year simulation was conducted to analyze the implementation of a PV system in an industrial setting. The study assessed energy savings, cost efficiency, and environmental benefits by modeling energy consumption, production, and storage dynamics. The financial feasibility of the investment was evaluated using key performance indicators such as return on investment, payback period, and levelized cost of electricity.ResultsThe findings demonstrate that PV systems significantly reduce electricity expenses and reliance on grid power, achieving a payback period of approximately 9.4 years. The company has the potential to significantly reduce CO2 emissions, contributing to environmental sustainability. The simulation further revealed that PV adoption enhanced energy independence, covering 53.3% of the company’s energy needs while minimizing operational costs.DiscussionThe study highlights PV technology’s economic and environmental benefits in industrial applications. Energy storage integration optimizes energy utilization, increasing efficiency and financial viability. These findings provide valuable insights for construction companies considering renewable energy investments. The broader societal advantages, including CO2 reduction, improved public health, and regulatory compliance, underscore the importance of transitioning toward sustainable energy solutions.